Research on weakly conservative passive fault-tolerant control method considering the fault distribution - Dan Du; Zetao Li (Engineering Science and Technology, an International Journal)
This study proposes a weakly conservative passive fault-tolerant control method that considers the fault distribution. The concept of weakly conservative passive fault-tolerant control is introduced initially. For fault parameter uncertainty domains with low probability, the constraints of control design are relaxed to expand the feasible domain of passive fault-tolerant controller parameters. The aim of weakly conservative passive fault-tolerant control is to find the optimal controller in the passive fault-tolerant controller parameter feasible domain. Moreover, a weakly conservative passive fault-tolerant control method is designed based on guaranteed robust cost control. Compared to the fault parameter uncertainty domain with high probability, the corresponding upper limit constraint of the performance index is increased for the fault parameter uncertainty domain with low probability. Furthermore, a larger feasible domain of passive fault-tolerant controller parameters is structured. A weakly conservative passive fault-tolerant controller based on guaranteed robust cost control is derived from the feasible domain of the passive fault-tolerant controller parameter. The proposed method overcomes the strong conservatism of passive fault-tolerant control and has practical application value. The simulation results on a boost DC-DC converter validate the effectiveness of the proposed method.